Folk Art Crafts Of Kazakhstan: The Concept Of Renovation Of Industrial Buildings (Turkish Journal of Computer and Mathematics Education (TURCOMAT), 2021)
This article examines the issues of preserving and reviving the artistic traditions of folk applied art at a new level. The concept of spatial organization of the environment for the production of folk art products is proposed, taking into account their specific features of technological production. The main goal is to create an appropriate spatial environment for the high-quality production of elements of folk art craft, while preserving the historical and aesthetic categories of products that ensure their recognition as a work of art.